Phospholipidomic Analysis Reveals Changes in Sphingomyelin and Lysophosphatidylcholine Profiles in Plasma from Patients with Neuroborreliosis. Issue 1 (10th November 2016) - Łuczaj, W.; Domingues, P.; Domingues, M. R.; Pancewicz, S.; Skrzydlewska, E.
Abstract: In recent years, the number of patients suffering from Lyme Disease (LD) has significantly increased. The most dangerous manifestation of LD is neuroborreliosis associated with invasion of the central nervous system by Borrelia burgdorferi . Phospholipids (PL) and their metabolites are involved in inflammation, which plays a dominant, but still unclear, role in the pathogenesis of neuroborreliosis. We analyzed the plasma PL profiles of neuroborreliosis patients ( n = 8) and healthy volunteers ( n = 8) using a lipidomic approach. Significant increases in the lysophosphatidylcholines LysoPtdCho 16:0 and LysoPtdCho 18:2 were observed. The plasma of neuroborreliosis patients appeared to have an increased relative abundance of sphingomyelin CerPCho d18:1/24:1 and a decrease in CerPCho d18:0/18:0. Principal components analysis of the relative abundances of all PL class species distinguished between neuroborreliosis patients and healthy subjects. This is the first report comparing PL classes and their molecular species in neuroborreliosis patients and healthy subjects.